Pseudo Weakly Closed Submodules and Related Concepts - Mohammadali, Haibat K.; Dahash, Mohammad E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Let  be a commutative ring with identity, and  be a unitary left -module. In this paper we introduce the concept pseudo weakly closed submodule as a generalization of -closed submodules, where a submodule  of an -module  is called a pseudo weakly closed submodule, if for all , there exists a -closed submodule  of  with  is a submodule of  such that . Several basic properties, examples and results of pseudo weakly closed submodules are given. Furthermore the behavior of pseudo weakly closed submodules in class of multiplication modules are studied. On the other hand modules with chain conditions on pseudo weakly closed submodules are established. Also, the relationships of  pseudo weakly closed submodules with other classes of modules are discussed.